Analysis of Mut'ah Marriage Hadith from Sunni & Shia Perspective - Hasyim, Badruzzaman; Ramadhita, Ramadhita (Fakultas Syariah (Syari'ah Faculty ), 2025)
In Islam, marriage is considered as a strong bond between a man and a woman which aims to form a stable and lasting family as well as Sakinah, mawaddah, and rahmah. This marriage is considered as a valid contract between the two parties and has clear rules and obligations. However, opinions regarding mut'ah marriage differ among Islamic scholars and schools of thought. Some scholars hold that mut'a marriage is a permissible practice under certain circumstances, while others strictly prohibit it. This research is library research, this research is classified as qualitative research and to combine Sunni and Shia opinions, a comparative method is used. The results of this study are that the Sunnis agree that the law of mutah marriage is unlawful, while the Shiites argue that the law of mutah marriage is halal. This legal difference occurs because of differences in the interpretation of the hadiths they use in hujjah. Both Sunnis and Shiites have hadiths that strengthen their respective arguments.